GAMBARAN ANSIETAS KELUARGA SAAT MENGHADAPI KEKAMBUHAN ANGGOTA KELUARGA DENGAN PENYAKIT KRONIS - Livana PH; Sih Ayuwatini; Rita kartika Sari (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2018)
DETERMINE THE IMAGE OF FAMILY ANXIETY WHEN FACING THE RECURRENCE OF FAMILY MEMBERS WITH CHRONIC DISEASES ABSTRACTChronic illness is a condition (illness) that lasts for a long time and continuously. Some chronic diseases that exist in the community such as diabetes mellitus, hypertension, etc. The aims of this study to determine the image of family anxiety when facing the recurrence of family members with chronic diseases. This research is a descriptive quantitative research, with total sample 64 respondents. The level of family anxiety was measured using an anxiety-related DASS questionnaire consisting of 14 questions. The results showed that the majority families experienced anxiety at the level of moderate anxiety. The need for family and community-based health services to improve the ability of families in overcoming anxiety so as to care for family members with chronic diseases. Keywords: Anxiety, family, chronic illness